ANALISIS PERAN ANGGARAN PENJUALAN DALAM MENINGKATKAN EFEKTIVITAS PERENCANAAN LABA PERUSAHAAN - Sherin Aulia Putri; Stefani; Putri Chairunnisa Pane; Dini Vientiany (CV. Barokah Publsiher, 2025)
Anggaran bahan baku sangat penting dalam kerangka penganggaran perusahaan, terutama Sales budgeting is a key component in corporate financial planning as it serves as the basis for preparing other budgets, including cost and profit budgets. The accuracy of sales budgeting significantly affects the effectiveness of profit planning. This study aims to analyze the role of sales budgets in improving the effectiveness of corporate profit planning through a review of relevant academic journals. The research method employed is a literature review by examining twelve national journals discussing sales budgeting, sales forecasting, and profit planning. The results indicate that sales budgets play a crucial role as the foundation of profit planning, a managerial control tool, and a means of evaluating profit achievement. Furthermore, accurate sales forecasting and the integration of sales budgets into comprehensive budgeting systems enhance the effectiveness of profit planning. Therefore, companies should prepare sales budgets systematically and data-driven to achieve optimal profit targets.